Triple Helix for Sustainable Development Goals: An Impact Assessment of Shared Service Facility for Micro, Small, and Medium Enterprises Competitiveness in the Philippines - Armas, Kenneth L.; Cruz, Catherine Dela; Navarro, Jonas Emmanuel; Viloria, Vivien (International Review of Management and Marketing, 2024)
This study investigates the impact and operational challenges of the Shared Service Facility (SSF) for Micro, Small, and Medium Enterprises (MSMEs) in the Philippines, focusing on enhancing MSME competitiveness and sustainability. Through a mixed-methods approach, including surveys, interviews, and data analysis, the study assesses the SSF’s effectiveness in supporting MSMEs and identifies key challenges hindering its operation. The findings reveal significant improvements in MSMEs’ access to resources, innovation capacity, and market competitiveness following SSF assistance. However, logistical, managerial, and resource-related challenges pose significant hurdles to the SSF’s operational efficiency and effectiveness. To address these challenges, a comprehensive Strategic Plan is formulated, outlining key actions to improve logistical efficiency, enhance managerial effectiveness, strengthen financial sustainability, upgrade technological infrastructure, and foster collaboration and partnerships. Implementation of these strategic initiatives is crucial for optimizing the SSF’s operation, enhancing its impact on MSME competitiveness, and ensuring long-term sustainability. Overall, this study contributes valuable insights into the role of the SSF in fostering MSME development and economic growth in the Philippines, highlighting the importance of targeted interventions and collaborative efforts to support inclusive and sustainable development.